In-plane Shear Strengthening of Unreinforced Masonry Walls Using GFRP Jacketing - Mustafaraj, Enea; Yardim, Yavuz (Periodica polytechnica. Civil engineering. Bauingenieurwesen, 2017)
In this paper, it is presented the experimental results of a campaign on diagonal compression tests, as of ASTM E519-02, to assess and compare the in-plane behavior of standard size of 1200 × 1200 × 250 mm, for three unreinforced and three reinforced wall panels by glass fiber reinforced polymer (GFRP) embedded in an inorganic matrix.From the diagonal compression test results, were determined some of the main mechanical parameters such as: shear strength, modulus of rigidity and ductility, before and after application of the reinforcement.The experimental results showed that the GFRP reinforced panels exhibited a significant increase of 127% in shear resistance, 1100% in ductility and 650% in modulus of rigidity when compared to unreinforced panels.It was concluded that this technique provided satisfactory results and can be considered a suitable method for repair of masonry structures.